Sistem Informasi Pencarian Pekerjaan Sampingan (Side Jobs) Menggunakan Metode Agile - Sanudin Sanudin; Indah (Jurnal SIGMA, 2022)
The increase in basic needs encourages people to seek more income for the sake of a decent life. The income earned from working as a laborer is felt to be unable to meet basic needs, or the unemployed are waiting for an opportunity to work in a company. Hobbies and skills or abilities of each individual, of course, vary according to their respective interests. Hobbies that are done unconsciously, turn into skills or abilities that can actually help lighten the burden on other people. The community needs side jobs with the ease of finding customers through an information system that can be easily accessed via the internet in the form of an application. Currently the use of the internet has become a basic necessity, both for daily life and business activities. This study aims to create a WEB-based part-time job search application using the PHP programming language using the Agile development method which is expected to increase job opportunities based on individual abilities. Keyword: Income, Job, Internet, WEB, PHP, Agile